1992
DOI: 10.1159/000177708
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Iron from a Traditional Tunisian Meal with Chickpeas Fed to Healthy Rats

Abstract: The influence of a diet of couscous with chickpeas, a traditional Tunisian meal, or one providing iron as ferrous sulfate, on the utilization of 59Fe was evaluated in studies with rats. The iron content of the couscous and chickpea preparation was 30 mg/kg dry weight. There was no difference in the relative absorption of iron from ferrous sulfate or couscous with chickpeas, suggesting that iron from this preparation may be a good dietary source of nonheme iron for rats. Couscous and chickpeas consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…In the same way, green tea significantly inhibited iron absorption, but this inhibitory effect was less marked than that of black tea. The iron absorption from couscous without tea is simi lar to our previous data findings in couscous with chick-peas [8].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the same way, green tea significantly inhibited iron absorption, but this inhibitory effect was less marked than that of black tea. The iron absorption from couscous without tea is simi lar to our previous data findings in couscous with chick-peas [8].…”
Section: Discussionsupporting
confidence: 89%
“…Samples and tracer doses of radioactivity measure ment were counted on a Packard Auto-gamma Scintil lation spectrometer 5320, and iron absorption was cal culated according to the following formula [8]: …”
Section: Measurement O F Radioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of dietary iron bioavail ability using extrinsic labeling techniques in both rats and humans was reported in several studies [8][9][10][11][12]. Forbes et al [15] found an excellent agreement between nonheme iron absorption measured by an isotopic method and other methods using an unlabeled source iron in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that there was no difference in absorption of iron by rats from the two sources suggests that iron from couscous with chickpeas may be a good dietary source of nonheme iron for rats [8], However, the iron absorption from another typical Tunisian meal 'couscous' with vegetables including chickpeas in rats, using similar methodology, was similar to the previous findings in cous cous with chickpeas, but the administration of graded amounts of black and green tea pre pared under realistic Tunisian circumstances dramatically decreased the nonheme iron bio availability from couscous [9]. Rossander et al [10] reported that iron absorption was low er from a cereal-milk meal than from meals containing orange juice or bacon but higher than that from meals containing tea or choco late milk.…”
Section: Introductionmentioning
confidence: 99%